Costos de producción para la elaboración de calzado y su efecto en la rentabilidad de la empresa artesanal Juan Arias de Guayaquil, año 2014 - Fuertes Sojos, Pamela Karina (2015)
The purpose of this research is to identify costs in making handmade footwear company Juan Arias, of the city of Guayaquil in the period 2014 for analyzing the accounting information to calculate and determine the profitability of production 11,000 pairs of shoes for women. For the study and development of the research was carried out with the collaboration owner and staff of the company, which allowed it to be feasible to obtain the data and results. It is noteworthy that the company does not have an accounting system and it does not handle a model of cost control; so the information provided both costs and expenses, such as the resources used for the production are estimated values as empirically made the register of economic activities. Although they have an outside accountant, he is only responsible to handle formalities for the fulfillment of fiscal and social obligations. Whereas for achieving the objectives of the investigation and depending on the source information, techniques used, procedures and methods of study, which identified each of the costs of raw materials, labor and manufacturing overhead costs and as operating expenses involved in the process of making shoes, and thus able to calculate the production costs totaling $ 102,616.88, unit costs of production is $ 9.33 likewise income $ 186,185 settled 60 in relation to the sales gain that helped break even, plus the financial statements were made, and the values reflected the real profitability of the company 13.63% was determined, as well as allowed to conclude and recommend